Gale encyclopedia of everyday law - Wilson, Jeffrey 1971-; Gale Group (Detroit, Mich. Gale, 2006)
This encyclopedia fills a much-needed gap between legal texts focusing on the theory and history behind the law and more practical guides dealing with the law and its everyday effect upon its citizens. Containing approximately 200 articles, the Encyclopedia includes: brief descriptions of each issue's historical background, covering important statutes and cases; profiles of various U.S. laws and regulations; and details of how laws and regulations vary from state to state.
v. 1. Americans with Disabilities Act to family law -- v. 2. First Amendment law to travel.
Electronic reproduction.
Keywords: Law -- United States -- Popular works; Electronic books